Karakteristik Granul Gastroretentive Mukoadhesif Amoksisilin dengan menggunakan Kitosan-Alginat, Na.CMC dan HPMC: Characteristics of Gastroretentive Mucoadhesive Granules Amoxicillin using Chitosan-Alginate, Na.CMC and HPMC - Siti Rofi’ah Febryani; Sabaniah Indjar Gama; Angga Cipta Narsa (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Gastroretentive Drug Delivery System (GRDDS) is a slow-release preparation that can be bound to the surface of epithelial cells or gastric mucosa, while mucoadhesive is one of the mechanisms of action of the Gastroretentive Drug Delivery System (GRDDS), which is a drug delivery system in which the bio adhesive polymer is combined with the drug. designed to have a longer contact with the mucous membranes in the digestive tract. This study aims to see how the characteristics of the granules that are formulated in the form of mucoadhesive gastroretentive granules. The preparation method used was wet granulation using a mucoadhesive polymer, namely chitosan-alginate with the addition of HPMC and Sodium CMC. The results showed that the velocity test of the flow rate on the granule formula F1-F8 met the flow rate requirements, the results of the F9 velocity had a poor flow rate, while the results of the angle of repose measurement in the F1, F2 and F4 formulas had good flowability, which was below 30o, different with F3, F5, F6, F7, F8, and F9 which have a 30-40o angle of repose with good flowability. The results of the particle size distribution using the stratified sieve method showed that the formulas F1-F9 were mostly retained by a mesh number 20 sieve with a size of 426-850 m. The results of the test results of the gastroretentive mucoadhesive granule preparation of amoxicillin showed that the preparation met the requirements for making granules.